Evelyn J Hinz (ed): Diet and Discourse: Eating, Drinking and Literature - Davidson, Alan E (Petits Propos Culinaires, 2024)
Evelyn J Hinz (ed): Diet and Discourse: Eating, Drinking and Literature, being issue 24/3-4 (summer/fall, 1991) of Mosaic (a journal for the inter-disciplinary study of literature): University of Manitoba, Winnipeg, 1991: 278 pp, no index, bibliographical references attached to each essay, no information about the cost of back numbers (which this presumably now is), but write to Business Office, MOSAIC, 208 Tier Building, University of Manitoba, Winnipeg MB, Canada R3T 2N2.